Age- and sex-based ranges of platelet count and cause-specific mortality risk in an adult general population: prospective findings from the Moli-sani study. (3rd April 2018) - Bonaccio, Marialaura; Di Castelnuovo, Augusto; Costanzo, Simona; De Curtis, Amalia; Donati, Maria Benedetta; Cerletti, Chiara; de Gaetano, Giovanni; Iacoviello, Licia
Abstract: Platelet count varies by age, sex and ethnicity. However, previous studies have adopted standard ranges to identify subjects with thrombocytopenia or thrombocytosis. The aim of this study was to test the predictive role of age-sex-based cut-offs of platelet count proposed by an Italian collaborative study, towards the risk of cause-specific death. We conducted a prospective analysis on 21, 563 adult subjects (mean age 55.6 ± 11.8) randomised from the general population of the Moli-sani study. Hazard ratios (HR) were calculated by multivariable Cox-proportional hazard models with 95% confidence intervals. Over a median follow-up of 8.2 years (interquartile range: 7.3 to 9.2 years; 175, 972 person-years), we ascertained and validated 1, 130 deaths, 415 of which are from cardiovascular disease, 439 from cancer and 276 from non-vascular/non-cancer causes. As opposed to the normal ranges defined by age and sex (extreme values from 122 to 405 x10 9 /L), lower platelet number (87.7% of values being higher than 100x10 9 /L) was associated with increased risk of total (HR = 1.92; 95%CI 1.38–2.67), cancer (HR = 1.77; 95%CI 1.03–3.05), and non-cardiovascular/non-cancer mortality (HR = 3.16; 95%CI 1.84–5.42) but was unrelated to cardiovascular mortality. Higher platelet count was not associated with any death risk. In conclusion, age-sex-based low platelet count, well above the traditional lower normal range of <100 x10 9 /L, is associated with increased total and specific mortality risk in a general population.